The role of sucrose during maturation of black spruce (Picea mariana) and white spruce (Picea glauca) somatic embryos - Iraqi, D; Tremblay, F.M. (Laval Univ., Ste-Foy (Canada)) (Physiologia plantarum, 2001)
The present study was conducted to understand the role of sucrose in the medium on the maturation of black spruce and white spruce somatic embryos. A maturation medium containing 6% sucrose, which hydrolyzed into glucose and fructose, gave significantly more embryos than a medium containing 3.16% of each glucose and fructose. Preventing the complete sucrose hydrolysis by a daily transfer of the tissues onto fresh medium significantly decreased the yield of somatic embryos compared to when sucrose was allowed to complete its hydrolysis. This reduction was not due to the manipulation of the tissues during the transfer, since a daily in situ transfer did not affect embryo production. To verify if the better embryo production observed on a medium containing 6% sucrose was due to the increasing osmotic pressure of the medium, this increasing osmotic pressure was simulated with a sequence of media containing different concentrations of glucose and fructose. Unexpectedly and for both species, this simulation did not improve somatic embryo production, which stayed similar to the one obtained on constant osmotic pressure. To understand these results, embryos produced on the different treatments were analyzed in terms of sucrose, glucose, fructose and starch levels and protein contents. The embryo carbohydrate content was independent from the carbohydrate used in the maturation medium. However, embryos matured on 6% sucrose allowed to hydrolyze during the maturation period contained significantly more soluble and insoluble proteins than embryos matured on any other treatment. Furthermore, embryos with a higher protein content also exhibited a higher epicotyl appearance frequency. The role of sucrose as a regulatory factor during the maturation of spruce somatic embryos is discussed.